2003
DOI: 10.1002/ijc.11263
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of tamoxifen and the farnesyl transferase inhibitor FTI‐277 on inhibition of MCF‐7 breast cancer cell‐cycle progression

Abstract: The efficacy of tamoxifen in the hormonal therapy of breast cancer is well established, but therapeutic resistance is inevitable. FTIs are a new class of anticancer drugs that are in phase III clinical evaluation. Since the mechanisms of action of these 2 classes of drugs are different, we tested the combination of tamoxifen and FTI-277 on inhibiting proliferation of hormone-dependent MCF-7 human breast cancer cells. An additive effect on cell proliferation was demonstrated, accompanied by an additive G 0 /G 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 59 publications
5
28
1
Order By: Relevance
“…In this study, only the dosage above 0.2 µM/l showed antiproliferative effects on MCF-7 cells. The effective dose reported here was higher than the value reported by Doisneau-Sixou et al (2003). RP-HPLC Fraction 30 of kefir mother culture extract significantly increased MCF-7 cell susceptibility to tamoxifen (Figure 10).…”
Section: Resultscontrasting
confidence: 62%
“…In this study, only the dosage above 0.2 µM/l showed antiproliferative effects on MCF-7 cells. The effective dose reported here was higher than the value reported by Doisneau-Sixou et al (2003). RP-HPLC Fraction 30 of kefir mother culture extract significantly increased MCF-7 cell susceptibility to tamoxifen (Figure 10).…”
Section: Resultscontrasting
confidence: 62%
“…Three other groups have since reported a similar interaction for FTIs with tamoxifen or aromatase inhibitors, and have suggested either a synergistic or an additive antitumor effect (Long et al 2004). One recent study implied an additive effect on G0/G1 cell-cycle arrest, and that the FTI-277, when combined with tamoxifen, maintained higher levels of the cdk inhibitor p21 waf/cip1 , resulting in an additive effect on inactivation of cyclin E/Cdk2 complexes and decreased phosphorylation of pRb (Doisneau-Sixou et al 2003).…”
Section: Enhanced Anticancer Effects For Stis In Combination With Endmentioning
confidence: 99%
“…Moreover, we are in the situation of patients who are in progression on tamoxifen therapy at the initiation of the combination treatment, whereas the patients of the former study already showed resistance to tamoxifen but could respond to letrozole alone. We and others previously showed the additive or synergistic action of a combination of tamoxifen with a FTI to inhibit proliferation and promote apoptosis in vitro and in vivo (9,(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…This trial showed good tolerability and objective response (OR) rates of 10% and 14%, respectively, with an additional 15% and 9% clinical benefit (CB) rate in 41 and 35 patients, respectively (12). We (13,14) and other (9) showed that FTIs combined with endocrine therapy have additive or synergistic effects on the antiproliferative effects on MCF-7 cells and in xenografts (15). We then hypothesized that the combination of tamoxifen and tipifarnib may benefit metastatic breast cancer patients.…”
mentioning
confidence: 88%